Air‐breathing ecology of Arapaima sp.: Conservation implications for an imperilled fish. Issue 6 (27th April 2021) - Stokes, Gretchen L.; Castello, Leandro; Petersen, Thiago A.; Cooke, Steven J.; Power, Michael; Zuanon, Jansen; Martins, Eduardo G.
Abstract: Arapaima ( Arapaima sp.) are highly overexploited fish endemic to the Amazon basin. Because the fish are obligate air‐breathers, it is possible to use surface‐breathing events to count individuals visually for population censuses important for conservation, yet uncertainties remain about body size and environmental influences on air‐breathing intervals, and thus count accuracy. This study examined relationships between breathing intervals and environmental parameters (e.g. water temperature and transparency) and body size for radio‐tagged arapaima ( n = 12) in an upland river‐floodplain (Lake Ayapuá, Amazonas, Brazil). Generalized additive mixed models were used to evaluate environmental, size, and behavioural correlates of breathing intervals. Temperature was the most influential predictor of air‐breathing intervals, followed by body size. The shortest breathing intervals were associated with consecutive 'aggressive' breaths while the longest breathing intervals had consecutive 'calm' breaths. Type of breath, size, and temperature predictors revealed that breathing intervals ranged from 4 to 46 min and were not significantly different among life stages ( x ¯ = 15.9 min for sub‐adults and adults (>1 m); x ¯ = 14.8 min for juveniles (<1 m)). Whereas the current population census method uses fish counts in 20‐min intervals, this study found that 15% of observed breaths, and two thirds of fish, took longer than 20 min to breathe. These findings were obtained in relatively cool‐water environments, so it is recommended that future population census methods consider water temperature (e.g. extend intervals used for counts in cooler waters), which may improve the accuracy of census counts and thus further enhance arapaima conservation efforts. This study demonstrated an effective method in which fundamental biological information is used to inform and improve population census methods for an imperilled fish in a region where traditional stock assessment is ineffective. Similar approaches for adaptive stock assessments could be applied to improve conservation of other air‐breathing fishes (e.g. lungfishes) globally.